A cobalt-aluminium layered double hydroxide with a nickel core-shell structure nanocomposite for supercapacitor applications - Edris Jamshidi; Samad Dalvand; Faranak Manteghi; Seyed Morteza Mousavi-Khoshdel (iScience)
Summary: Layered double hydroxides (LDHs) are promising structures in applications including supercapacitors, which are claimed to help in arresting environmental chaos by their ability in energy storing. In this work, a Co-Al LDH and its metallic Ni core-shell nanocomposite were prepared and described using Fourier transform infrared (FTIR), X-ray diffractometer (XRD), scanning electron microscopy (SEM), and transmission electron microscopy (TEM) techniques. The two materials were electrochemically examined. The specific capacitance in current density of 1 A g−1 was 90 C g−1 (341.75 F g−1) and 210 C g−1 (792.5 F g−1) for the LDH and its composite, respectively. Compared with similar composites, the specific capacitance, especially the composite has a larger value in the order of 1.08–5.82 of magnitude. Moreover, the cycle stability test shows a slow drop at current density 4 A g−1 within 3,000 cycles, meaning that for the pure hydroxide and its Ni composite, a loss of 21% and 10% of specific capacitance was observed, respectively.